Changing mindsets: A passive-first artificial sky - Haglund, Bruce; Edde, Emilie; Flesher, Daniel; Gomez, Brenda (ARCC Conference Repository, 2014)
Architectural design that meets the goals of Architecture 2030 or results in zero net-energy performance is most elegantly achieved when employing effective passive strategies before adding high-technology components. With this ideal in mind, I posed a research question to a graduate seminar in natural lighting, "Can an artificial sky for testing daylighting models be designed that uses only daylight, rather than electric lamps, as its lightsource?” My threefold motivation for the question was: (1) matching”use a passive device to test a passive system (daylighting), (2) quality”use high-quality daylight to test daylighting systems, and (3) energy”use a low-energy system for testing models of low-energy designs. Currently, all artificial skies use an array of fluorescent lamps to simulate sky conditions. These skies are solely mechanical systems, have color rendering capabilities far inferior to daylight, and consume thousands of kilowatt-hours of electricity. The seminar students were up to the task and developed and tested successful scale models of two basic types”mirror-box and conical. We chose to build the conical prototype because its geometry is unlike that of any existing skies. To further encourage a sustainability-sensitive mindset, we designed the sky to be made of modular, bolted segments for non-destructive deconstruction and easy reconstruction. The building phase of the project was completed by the end of Spring 2013, and testing commenced in Fall 2013. This paper reports on the actions necessary to make the prototype a viable tool for learning about daylighting from prototype construction, calibration, and adjustment to test equipment set-up; to a users’ manual describing how to employ useful test methods. In summary, the project not only focused on the design, fabrication, and testing of the sky, but is also about the change in mindset”valuing the efficient and elegant use of resources”required for a sustainable future stressing: (1) employing appropriate technologies for the task at hand (passive systems), (2) using high-quality resources (daylight), and (3) saving energy (100% lighting energy savings). The daylighted artificial sky serves as a hands-on exemplar, which has involved the collaboration of teams of students over a four-year span to design, develop, and test the artificial sky. To date about 30 students have participated in the project by answering the design question, writing and presenting research papers, designing and building the full-scale prototype, testing its performance, and, finally, testing their daylighting design proposals in the sky. Aspirationally, this shift in mindset will translate into the students’ future work in the design professions.